Modeling and Simulation for Integrating Four Reactors in the Continuous Catalytic Regeneration Reforming Process Using MATLAB. Issue 1 (July 2021) - Babaqi, Badiea S.; Takriff, Mohd S.; Othman, Nur Tantiyani A.; Abu Hasan, Hassimi; Mahmoudi, Ebrahim
Abstract: Modeling and simulation were developed of the continuous catalytic regeneration reforming process for integrating four reactors and studying the effecting operating parameters to improve the process performance. The process model included four reactors as stack and used to investigate the profiles of reformate composition products and research octane number. The main reactions that occur in reforming reactors included five reactions namely; dehydrogenation, dehydrocyclization, isomerization, hydrocracking and hydrodealkylation. The kinetic and thermodynamic parameters were estimated by the particle swarm optimization approach to monitor the process behavior. The expected results have been validated of the model simulation with comparison to data of actual plant, and average absolute deviation (AAD%) of two parameters; reformate composition and octane number reached 0.04% and 1.3%, respectively. This evaluation was a fair agreement and within the acceptable limit.